Sharing Location Information in Multi-UAV Systems by Common Channel Multi-Token Circulation Method in FANETs - DOĞAN, BUKET; ÜLKÜ, EYÜP EMRE; DEMİR, ÖNDER (KAUNAS UNIV TECHNOLOGY, 2019)
Unmanned Aerial Vehicle (UAV) technology is being used increasingly for military and civilian purposes. The primary reason for this increase is that UAVs eliminate the risk to human life in difficult and dangerous missions, are cost effective, and easily are deployed. Developments in UAV technology and decreasing costs have increased UAV usage. However, when multiple UAVs are deployed, inter UAV communication becomes complicated. For this reason, communication in multi-UAV systems is the most important problem that needs to be solved. To enable communication among UAVs without infrastructure support, a Flying Ad Hoc Network (FANET) is used. A FANET provides UAVs to fly in tandem without colliding. To ensure coordinated flight, UAVs require the location information of other UAVs. In this study, we developed a common channel multi-token circulation protocol to share location information in multi-UAV systems that communicate using a FANET. The proposed method ensures that UAVs in multi-UAV systems know each other's coordinate information with minimum error.
Keywords: Flying Ad Hoc networks (FANET); Mobile Ad Hoc networks; Multi-token circulation; Unmanned aerial vehicle (UAV)